Peran BPD Sebagai Mitra Pemdes dalam Meningkatkan Akuntabilitas Pengelolaan Dana Desa - Siti Rodiah; Intan Putri Azhari; R Septian Armel; Evi Marlina; Adriyanti Agustina Putri; Zul Azmi; Rama Gita Suci; Bustamin Bustamin; Rizda Akira Henur; Nadila Rahayu (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2021)
Accountability is very important in managing village funds. The Village Consultative Body is a village institution that has an important role as a partner of the village government in realizing and increasing the accountability of village fund management. This role starts from planning the allocation of village funds, implementing the program, to reporting as a form of accountability carried out by the village government. The problem that has occurred so far is the low mastery/understanding of BPD members on the importance of the BPD's role in realizing and increasing village fund management accountability. This service is carried out to improve the human resources of the BPD in Pulau Permai Village in understanding and applying the role of the BPD in creating accountability in the village. This activity was carried out at the Pulau Permai Village Meeting Building, Kec. Tambang District. Kampar. The approach taken is training and technical guidance, namely by providing an explanation of the material in tutorials and discussions.